Landscape and Heritage: Key Elements for Tourism Development in an Interior Space: The Case of Yecla (Murcia). - Morales-Yago, Francisco José (Revista de Estudios Andaluces, 2017)
This work analyzes the importance of landscape and patrimonial resources as a strategy for local development in interior spaces with little tourism activity, deepens the image of the landscape as a tourism product and proposes actions that will promote new sources of wealth and employment as well as paralysis of the threats that could contribute to the disappearance of these inherited cultural landscapes with a significant identity character. Through the SWOT methodology, the importance of actions and policies that address sustainability as a guarantee for a territorial balance that contemplates environmental preservation, economic viability and social equity in the development of benefits for the entire municipality and its area of influence.